Perkembangan Kurikulum 2013 ke Kurikulum Merdeka di SMK N 2 Magelang - Ramadhani, Ananda Putra (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
The development from the K13 curriculum to the independent curriculum has caused many significant changes. Many terms previously used in the 2013 curriculum are no longer used in the independent curriculum and have developed into new terms. The purpose of this study was to determine the development of the curriculum at SMKN 2 Magelang. The method used in this research is using a qualitative approach and also using a literature review method that allows for an in-depth understanding of the changes that have occurred in the accounting curriculum. Data was collected through interviews and observations in online studies available on the internet. The data analysis technique uses quantitative descriptive. The results of this study indicate that the development from curriculum 13 to the independent curriculum has caused many significant changes to the accounting curriculum at SMKN 2 Magelang. One of the significant changes is the emphasis on implementing a more contextual and project-based learning approach in teaching accounting. An independent curriculum also provides greater flexibility for schools in adapting the curriculum to the needs of students. The independent curriculum introduces competency-based learning with an emphasis on developing students' practical skills in accounting. Based on the results of existing research, it is hoped that it can add to a better understanding of competency-based curriculum development models and their impact on higher education.